Polyvinyl alcohol composite silicon oxide microcapsule temperature control material and preparation method thereof
By combining Pickering emulsification method and electrospinning technology, polyvinyl alcohol composite silica microcapsule temperature control material was prepared, which solved the problem of difficulty in combining radiation refrigeration materials and phase change energy storage materials in the prior art, and achieved efficient temperature control and low energy consumption.
Patent Information
- Application Number
- CN202510189474.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The prior art is difficult to combine radiation refrigeration materials and phase change energy storage materials into one whole, resulting in large energy consumption of temperature control and insufficient temperature adaptability of the material.
Through Pickering emulsification method and electrospinning technology, an emulsion coated with capric acid-stearic acid co-crystals of nanosilica was mixed with a polyvinyl alcohol solution to prepare a polyvinyl alcohol composite silica microcapsule temperature control material. The material has a "beaded" structure, combining the functions of radiation refrigeration and phase change energy storage.
The synergistic effect of radiation refrigeration reducing temperature and phase change energy storage buffering temperature shock is achieved, which significantly reduces the energy consumption of temperature control and improves the temperature adaptability of the material.
Smart Images

Figure CN119753948A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of temperature control materials, and in particular to a polyvinyl alcohol composite silicon oxide microcapsule temperature control material and a preparation method thereof. Background Art
[0002] Temperature is an important indicator of social production and life, and temperature management is a concern in many fields. For example, the storage and transportation of temperature-sensitive foods and medicines require temperature control through cold chains; the temperature of fabrics and buildings is controlled for human comfort, etc. Temperature control methods such as cold chain transportation and air conditioning cooling consume a lot of energy, which runs counter to today's demand for energy conservation. Therefore, passive temperature control technology and materials are widely researched and developed.
[0003] Latent heat storage and radiative cooling have attracted people's attention because of their characteristics of not requiring energy input and excellent temperature control effects. Latent heat storage can achieve energy peak shaving and valley flattening, which can not only effectively utilize renewable energy, but also realize the utilization of waste heat energy in the system. Radiative cooling can radiate heat to the ultra-cold outer space close to absolute zero through the atmospheric long-wave infrared transparent window (λ is in the range of 8 to 13 microns), causing the surface of the material to cool spontaneously. In order to minimize the energy input from the sun, the radiative cooling material is required to have good diffuse reflection ability.
[0004] The main temperature control methods currently available do not combine radiation refrigeration and phase change energy storage into a whole, and different materials have their own disadvantages. If radiation refrigeration materials and phase change energy storage materials can be flexibly combined to form a whole, and a system in which radiation refrigeration reduces temperature and phase change energy storage buffers temperature shocks is realized, then the temperature adaptability of the material will be greatly improved. Therefore, the production of a temperature control material that is easy to prepare, scalable, has low material cost, has a wide range of application scenarios, and is environmentally friendly and synergistic with radiation refrigeration and phase change energy storage will have a very broad market prospect. Summary of the invention
[0005] The purpose of the present invention is to provide a polyvinyl alcohol composite silicon oxide microcapsule temperature control material and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art, and then form a temperature control system that uses radiation refrigeration to reduce temperature and phase change energy storage to buffer temperature shock through a simple preparation process, thereby greatly reducing the energy consumption of temperature control.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] The present invention provides a method for preparing a polyvinyl alcohol composite silicon oxide microcapsule temperature control material, comprising the following steps:
[0008] An emulsion of capric acid-stearic acid eutectic coated with nano-silicon oxide was prepared by Pickering emulsification method;
[0009] mixing the emulsion with a polyvinyl alcohol solution to obtain an electrospinning solution;
[0010] The electrostatic spinning solution is subjected to electrostatic spinning treatment to obtain a spinning membrane, which is the polyvinyl alcohol composite silicon oxide microcapsule temperature control material.
[0011] As a further preference of the present invention, in the process of preparing the emulsion by Pickering emulsification method, the mass ratio of water to capric acid-stearic acid eutectic is (50:50)-(95:5), and the mass ratio of water to silicon oxide is (100:1)-(100:10).
[0012] More specifically, the physically mixed water, silicon oxide, and capric acid-stearic acid eutectic are directly emulsified into an emulsion at a rotation speed of 10000 r / min-20000 r / min by the Pickering emulsification method, and the high-speed shear emulsification time is greater than 2 minutes.
[0013] Under the raw material ratio of the present invention, the emulsion prepared by the Pickering emulsification method can be stable for 3-10 days without demulsification, and does not demulsify at a centrifugal speed of 3000r / min-8000r / min for 3min-10min. After mixing with the polyvinyl alcohol solution, the stability is further enhanced, and can be stable for more than 30 days, and does not demulsify at a centrifugal speed of 3000r / min-15000r / min for 3min-10min. Figure 1 The figures are the actual pictures of the emulsions of Examples 1, 2 and 3 of the present invention and the visual changes and microscopic changes of the emulsion of Example 1 before and after being thickened by polyvinyl alcohol.
[0014] As a further preferred embodiment of the present invention, the concentration of polyvinyl alcohol in the electrospinning solution is 4%-12%.
[0015] As a further preferred embodiment of the present invention, the concentration of the polyvinyl alcohol solution is 6%-15%. The polyvinyl alcohol is any type of water-soluble polyvinyl alcohol.
[0016] The polyvinyl alcohol solution is preferably prepared by the following steps: polyvinyl alcohol is stirred and swelled in cold water at a speed of 100-500 r / min for 1 hour, and then heated and stirred at a temperature of 20°C-100°C at a speed of 100-500 r / min (time ≥ 2 hours) until the polyvinyl alcohol is completely dissolved. Finally, the prepared solution is allowed to stand and defoam for 6-24 hours to obtain a polyvinyl alcohol solution.
[0017] As further preferred embodiment of the present invention, the capric acid-stearic acid eutectic is a eutectic obtained by mixing n-decanoic acid and stearic acid at 80-90°C.
[0018] As a further preferred embodiment of the present invention, the mass ratio of decanoic acid to stearic acid is (4:6)-(9:1).
[0019] As a further preference of the present invention, the electrospinning process uses a needle inner diameter of 0.25mm-0.84mm, a voltage of 20kV-50kV, a spinning solution injection speed of 1.0ml / h-2.0ml / h, a spinning distance of 10cm-25cm, and the final deposited film thickness is 300μm-1000μm.
[0020] The present invention also provides a polyvinyl alcohol composite silicon oxide microcapsule temperature control material prepared by the above preparation method.
[0021] The fiber diameter of the polyvinyl alcohol composite silicon oxide microcapsule temperature control material prepared by the present invention is 100nm-3μm, and the microcapsule diameter is 300nm-10μm; its double fixed structure is helpful to improve the thermal reliability of the capric acid-stearic acid eutectic.
[0022] Polyvinyl alcohol is widely used as a common industrial raw material. It has good solubility, thermal stability, chemical resistance, storage stability, processability, degradability and mechanical properties. It is non-toxic, harmless and environmentally friendly. Because of the large number of C-OH structures in its chemical structure, polyvinyl alcohol has a very high atmospheric window comprehensive emissivity and has great potential in applications related to radiation cooling. Inorganic particles such as silicon dioxide are low-cost, stable, non-toxic, harmless and pollution-free. Its chemical structure contains a large number of Si-O-Si structures, so it has a good atmospheric window comprehensive emissivity. In addition, silicon dioxide also has good reflection ability for solar radiation, which makes it have great potential in applications related to radiation cooling. Fatty acids are the main components of neutral fats, phospholipids and glycolipids. Fatty acids and their eutectics are non-toxic, harmless and pollution-free, with adjustable melting points and large latent heat storage capacity.
[0023] The polyvinyl alcohol composite silicon oxide microcapsule temperature control material film prepared by the present invention has a "beaded" structure with polyvinyl alcohol fibers of micro-nano size diameter as "chains" and silicon oxide microcapsules of micro-nano size diameter as "beads". The decanoic acid-stearic acid eutectic is doubly bound by the polyvinyl alcohol fibers and the silicon oxide shell layer, playing a phase change energy storage role in the material; polyvinyl alcohol and silicon oxide have high atmospheric window comprehensive emissivity, and the characteristics and microscopic morphology achieve high solar radiation comprehensive reflectivity, playing a radiation cooling effect in the material.
[0024] In the present invention, the Pickering emulsification method is a method of shearing and dispersing the mixed liquid using a high-speed shear dispersion device, so that the solid particles are spontaneously adsorbed to the oil-water interface to form an emulsion with good stability; the electrostatic spinning method is a method of using an electrostatic spinning device to make the liquid overcome the surface tension of the droplets under the action of a sufficiently large electric field force to form a jet stream, and evaporate the solvent in the process to form a solid fiber. The material preparation process of the present invention does not involve chemical reactions, water is the only solvent, and it is environmentally friendly. The materials used are low-cost and non-toxic, the process is simple, the performance is stable, and it is safe and efficient. The material can be widely used in food packaging, pharmaceutical packaging, human thermal management fabrics and other fields.
[0025] The present invention discloses the following technical effects:
[0026] The present invention utilizes the characteristics of polyvinyl alcohol, nano-silicon oxide and capric acid-stearic acid eutectic to combine the three materials into a whole, thereby preparing a temperature-control film with synergistic effects of phase change energy storage and radiation refrigeration. The material is scalable, low-cost, easy to prepare and environmentally friendly.
[0027] The polyvinyl alcohol composite silicon oxide microcapsule material prepared by the present invention can provide all-weather radiation refrigeration and phase change energy storage, with a solar radiation comprehensive reflectivity of 85%-93% and an atmospheric window comprehensive emissivity of 93%-98%, and can achieve a temperature reduction of 0-8°C below the environment, with an average cooling power of 20W / m 2 -80W / m 2 The latent heat storage is 20J / g-70J / g and it still has good thermal reliability after 500-1000 temperature cycles.
[0028] The invention has simple process, stable performance, safety, high efficiency and low cost, and can be widely used in the fields of food, medicine, textile and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 The actual pictures of the emulsions of Examples 1, 2, and 3 of the present invention and the visual changes and microscopic changes of the emulsion of Example 1 before and after being thickened by polyvinyl alcohol;
[0031] Among them, a is a physical picture of the emulsion of Example 1, b is a physical picture of the emulsion of Example 2, and c is a physical picture of the emulsion of Example 3; d is the bright field and fluorescence field images of the emulsion in Example 1 before and after thickening by polyvinyl alcohol under a laser confocal microscope on the 0th day and the 30th day (gray is bright field, red is fluorescence field), and e is the visual changes of the emulsion in Example 1 before and after thickening by polyvinyl alcohol after standing for 0 days, standing for 10 days, standing for 30 days, and centrifuging at 5000 r / min for 3 minutes.
[0032] Figure 2 The actual image (a) and the microscopic morphology under a scanning electron microscope (b) of the electrospun film of Example 1 of the present invention are shown.
[0033] Figure 3 The temperature difference effect diagram of the electrospun film of Example 1 of the present invention and the plastic cling film under direct sunlight in the blueberry temperature protection simulation experiment; (a) is the FLIR image, and (b) is the actual image; in (a) and (b), the left side is the plastic cling film, and the right side is the electrospun film of Example 1 of the present invention.
[0034] Figure 4 The actual image (a) and the microscopic morphology under a scanning electron microscope (b) of the electrospun film of Example 2 of the present invention are shown.
[0035] Figure 5 The temperature difference effect diagram of the electrospun film of Example 2 of the present invention and the plastic cling film under direct sunlight in the blueberry temperature protection simulation experiment; (a) is the FLIR image, and (b) is the actual image; in (a) and (b), the left side is the plastic cling film, and the right side is the electrospun film of Example 2 of the present invention.
[0036] Figure 6 The actual image (a) and the microscopic morphology under a scanning electron microscope (b) of the electrospun film of Example 3 of the present invention are shown.
[0037] Figure 7 The temperature difference effect diagram of the electrospun film of Example 3 of the present invention and the plastic cling film under direct sunlight in the blueberry temperature protection simulation experiment; (a) is the FLIR image, and (b) is the actual image; in (a) and (b), the left side is the plastic cling film, and the right side is the electrospun film of Example 3 of the present invention. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] Example 1
[0044] A preparation method of polyvinyl alcohol composite silicon oxide microcapsule temperature control material:
[0045] (1) 1799 polyvinyl alcohol solid and deionized water were stirred at a mass ratio of 6:45 at a speed of 200 r / min at room temperature for 1 h, and then stirred and dissolved in an oil bath at a temperature of 100° C. and a speed of 300 r / min for 2 h to obtain a polyvinyl alcohol solution.
[0046] (2) Decanoic acid and stearic acid were dissolved and stirred in an oil bath at a temperature of 80° C. and a speed of 300 r / min in a mass ratio of 8:2 for 2 h to obtain fatty acid eutectics.
[0047] (3) Deionized water, 15 nm silicon dioxide powder and the fatty acid eutectic prepared in step (2) were mixed in a mass ratio of 6:0.36:4, and emulsified for 3 min at a speed of 12000 r / min using a digital disperser to obtain an emulsion.
[0048] (4) The emulsion prepared in step (3) and the polyvinyl alcohol solution prepared in step (1) were mixed in a mass ratio of 15.54:51, and stirred at a speed of 300 r / min for 2 h to obtain a spinning solution, wherein the concentration of polyvinyl alcohol in the spinning solution was 10%.
[0049] (5) The spinning solution prepared in step (4) was electrospun using an electrospinning device to prepare a spinning film. Aluminum foil was attached to the surface of the drum receiver. The spinning voltage was 32 kV, the receiving distance was 15 cm, the injection speed was 1.4 mL / h, and the needle model was 22 G. After spinning, the film was peeled off from the aluminum foil to obtain a "beaded" electrospun film with a thickness of 800 μm.
[0050] The electrospun film prepared in Example 1 of the present invention has a solar radiation comprehensive reflectivity of 86.8% and an atmospheric window comprehensive emissivity of 95.5%, and can achieve a temperature reduction of 3.7°C below the ambient temperature and an average cooling power of 37.4W / m 2 , indicating that the film has good radiative cooling ability. The latent heat storage of the film is 54.9 J / g. Compared with the film without temperature cycling, the latent heat storage value error of the film after 500 temperature cycles is less than 10%, indicating that the film has good thermal reliability.
[0051] The test method is as follows:
[0052] Diffuse reflection test was performed using UV / visible / near infrared spectrophotometer in integrating sphere mode, with BaSO4 white board as reference. m The calculation formula is:
[0053]
[0054] Where R(λ) is the spectral reflectance of the material, I s (λ) is the solar spectrum intensity, λ1 = 0.28 μm, λ2 = 2.50 μm. The data is taken from ASTM G173-03 (2020) and is the standard solar spectrum irradiance distribution when the air mass is AM1.5.
[0055] The emissivity test was performed using a Fourier transform infrared spectrometer. The test method was an indirect method in spherical integration mode, i.e., emissivity = 1-transmittance (spherical integration)-reflectivity. m The calculation formula is:
[0056]
[0057] Where ε(λ,T) is the spectral emissivity of the material at temperature T, I b(λ,T) is the spectral emissivity of the black body at temperature T, λ1=8μm, λ2=13μm.
[0058] The temperature reduction and average cooling power test were conducted on a self-made platform. A piece of polystyrene was used as the experimental platform, and a 25cm×25cm×5cm (length×width×height) cavity was cut in the center of the test platform. The sample and the thermocouple were placed in the cavity. The sample was temperature compensated by the thermocouple, and the heating power obtained was used as the measured net radiation cooling power of the sample. The temperature difference generated by the cooling of the experimental group samples was obtained by reading the surface temperature of several groups of samples and comparing them. The temperature reduction and average cooling power were taken as the average value within 24 hours.
[0059] Specifically: Two identical spinning membranes (50mm×50mm×0.5mm) were placed side by side at the bottom of the chamber. The two films were named sample 1 and sample 2. Sample 1 was tightly fitted on an aluminum film (50mm×50mm×1mm) above a silicone rubber heater (50mm×50mm×2mm, 24V, 6W). The heater was supported by four wooden pillars. Air was used as a heat transfer medium between the silicone rubber heater and the PS foam to avoid heat loss downward from the heater. Each pillar was 5mm high and 2mm in diameter. Thermocouple 1 (±0.1℃) was fixed below sample 1 to measure its temperature (T1) over time. The silicone rubber heater was controlled by a thermal feedback control program to keep T1 approximately equal to the ambient temperature T2. The power of the silicone rubber heater changed over time, and its value was automatically recorded by the program. The time-varying ambient temperature T2 is measured by a second thermocouple 2 (±0.1°C), which is fixed next to sample 1 in a place not exposed to direct sunlight, with no aluminum foil or sample on the surface, and reads the air temperature as the ambient temperature. T1 fluctuates with T2 due to the energy supply of the silicone rubber heater. That is, the heater compensates for the energy lost by radiative cooling, so the power of the silicone rubber heater represents the net radiative cooling power of the sample. A third thermocouple 3 (±0.1°C) is fixed below sample 2 to measure its time-varying temperature (T3). Sample 2 is the same as sample 1, except that the silicone rubber heater is turned off. Under sunlight, T3 represents the sample temperature below the ambient temperature, and T1-T3 represents the temperature difference generated by the film relative to the environment through radiative cooling.
[0060] The thermal properties (latent heat storage test) of the "beaded" electrospun film and PVA / emulsion cast film were tested using a differential scanning calorimeter. The temperature test range was -50°C to 50°C, and the melting temperature, crystallization temperature, melting enthalpy and crystallization enthalpy were measured. Three parallel samples were set up in the experiment, and the mean was used as the result, and the standard deviation was used as the error bar. The encapsulation rate R is expressed as:
[0061]
[0062] Where ΔH m,Flim represents the melting enthalpy of the film, ΔH m,PCM represents the melting enthalpy of the phase change material CS eutectic, k is the mass ratio of the phase change material to the dry weight of the film, k = 6 / 12.54 = 0.478.
[0063] The "beaded" electrospun film and PVA / emulsion cast film were placed in a temperature cycle box for thermal reliability testing. The program setting is: adjust the temperature in the box to -20℃. The temperature in the box is heated to 50℃ and maintained for 5min. The temperature in the box is lowered to -20℃ and maintained for 5min. Steps 2 and 3 are recorded as one temperature cycle. The temperature cycle in the box is specified for a certain number of times, the heating rate is about 3-5℃ / min, and the cooling rate is about 2-3℃ / min. Each temperature cycle lasts about 70min, and the upper and lower limits of the temperature can ensure that the melting point and crystallization point of the material are passed. Sufficient heating and cooling time can allow the material to undergo a complete phase change cycle. When the number of cycles reaches 100, 300 and 500 times, some "beaded" electrospun films and PVA / emulsion cast films are taken for differential scanning calorimetry testing, and the test method is the same as above.
[0064] Figure 2 (a) is a physical picture of the electrospun film of Example 1 of the present invention and (b) is a microscopic morphology picture under a scanning electron microscope.
[0065] The fiber diameter of the electrospun film prepared in Example 1 of the present invention is in the range of 100 nm-3 μm, and the diameter of the microcapsule is in the range of 300 nm-10 μm.
[0066] Blueberry protection simulation experiment: The blueberry variety selected in the experiment was Chungao blueberry produced in Yunnan, which was picked from the farm and immediately transported to the laboratory on the same day. Plastic boxes were selected as storage containers, cleaned and dried in a sterile operating table under a UV sterilizer. In order to simulate the actual conditions of commercial temperature at the retail end and refrigerated storage at the consumer end, the temperature of the artificial climate box was set to 10°C and the humidity was 66% rh. Blueberry fruits with no obvious mechanical damage and similar shapes and sizes were selected and randomly divided into two groups for preservation experiments, namely the experimental group and the control group. The blueberries in the experimental group were wrapped with a "beaded" electrospun film, stored in a plastic box, placed in an artificial climate box with the lid closed, and opened at 11 o'clock every day and placed in the sun for 1 hour, simulating the natural conditions under sunlight to verify the thermal protection of the spinning film on blueberries. The blueberries in the control group were wrapped with PE plastic wrap and placed in a plastic box, placed in an artificial climate box with the lid closed, and opened at 11 o'clock every day and placed in the sun for 1 hour, simulating the preservation effect of blueberries under possible actual storage conditions. The experimental group and the control group were stored and tested simultaneously. Except for wrapping with different films, other experimental conditions were the same. The surface temperature of the experimental group and the control group under direct sunlight was read by an infrared camera at 12 o'clock every day, and the temperature difference after 1 hour of irradiation was studied.
[0067] Figure 3 The temperature difference effect diagram of the electrospun film of Example 1 of the present invention and the plastic cling film under direct sunlight in the blueberry temperature protection simulation experiment; (a) is the FLIR image, and (b) is the actual image; in (a) and (b), the left side is the plastic cling film, and the right side is the electrospun film of Example 1 of the present invention.
[0068] Example 2
[0069] A preparation method of polyvinyl alcohol composite silicon oxide microcapsule temperature control material:
[0070] (1) 1788 type polyvinyl alcohol solid and deionized water were stirred at a mass ratio of 6:51 at a speed of 200 r / min at room temperature for 1 hour, and then dissolved and stirred in an oil bath at a temperature of 80° C. and a speed of 300 r / min for 2 hours to obtain a polyvinyl alcohol solution.
[0071] (2) Decanoic acid and stearic acid were dissolved and stirred in an oil bath at a temperature of 80° C. and a speed of 300 r / min in a mass ratio of 8:2 for 2 h to obtain fatty acid eutectics.
[0072] (3) Deionized water, 30 nm silica powder, and the fatty acid eutectic obtained in step (2) were mixed in a mass ratio of 9:0.5:1, and emulsified for 3 min at a speed of 18000 r / min using a digital disperser to obtain an emulsion.
[0073] (4) The emulsion obtained in step (3) and the polyvinyl alcohol solution obtained in step (1) were mixed in a mass ratio of 21:57, and stirred at a speed of 300 r / min for 2 h to obtain a spinning solution, wherein the concentration of polyvinyl alcohol in the spinning solution was 8%.
[0074] (5) The spinning solution prepared in step (4) is electrospun using an electrospinning device to prepare a spinning film. Aluminum foil is attached to the surface of the drum receiver. The spinning voltage is 30 kV, the receiving distance is 20 cm, the injection speed is 1.8 mL / h, and the needle model is 25 G. After spinning, the film is peeled off from the aluminum foil to obtain a "beaded" electrospun film with a thickness of about 500 μm.
[0075] The electrospun film prepared in Example 2 of the present invention has a solar radiation comprehensive reflectivity of 88.4%, an atmospheric window comprehensive emissivity of 97.3%, can achieve a temperature reduction of 7.1°C below the ambient temperature, and an average cooling power of 68.7W / m 2 , indicating that the film has good radiative cooling capabilities. The film has a latent heat storage of 28.8 J / g. The error in the latent heat storage value of the film after 1000 temperature cycles is less than 10% compared to the film without temperature cycles, indicating that the film has good thermal reliability.
[0076] Figure 4 The actual image (a) and the microscopic morphology under a scanning electron microscope (b) of the electrospun film of Example 2 of the present invention are shown.
[0077] The fiber diameter of the electrospun film prepared in Example 2 of the present invention is 100 nm-3 μm, and the diameter of the microcapsule is 300 nm-10 μm.
[0078] Figure 5 FLIR image (a) and actual image (b) comparing the temperature difference effect of the electrospun film prepared in Example 2 of the present invention under direct sunlight.
[0079] Example 3
[0080] A preparation method of polyvinyl alcohol composite silicon oxide microcapsule temperature control material:
[0081] (1) 1750 type polyvinyl alcohol solid and deionized water were dissolved and stirred at a mass ratio of 6:78 at a speed of 300 r / min at room temperature for 2 h to obtain a polyvinyl alcohol solution.
[0082] (2) Decanoic acid and stearic acid were dissolved and stirred in an oil bath at a temperature of 80° C. and a speed of 300 r / min in a mass ratio of 8:2 for 2 h to obtain fatty acid eutectics.
[0083] (3) Deionized water, 30 nm silica powder, and the fatty acid eutectic obtained in step (2) were mixed in a mass ratio of 8:0.5:2, and emulsified for 3 min at a speed of 15000 r / min using a digital disperser to obtain an emulsion.
[0084] (4) The emulsion obtained in step (3) and the polyvinyl alcohol solution obtained in step (1) were mixed in a mass ratio of 21:84, and stirred at a speed of 300 r / min for 2 h to obtain a spinning solution, wherein the concentration of polyvinyl alcohol in the spinning solution was 6%.
[0085] (5) The electrospinning film was prepared using an electrospinning device, with aluminum foil attached to the surface of the drum receiver, the spinning voltage was 25 kV, the receiving distance was 15 cm, the injection speed was 2.0 mL / h, and the needle model was 20 G. After spinning, the film was peeled off from the aluminum foil to obtain a "beaded" electrospinning film with a thickness of about 300 μm.
[0086] The electrospun film prepared in Example 3 of the present invention has a solar radiation comprehensive reflectivity of 87.4%, an atmospheric window comprehensive emissivity of 96.1%, can achieve a temperature reduction of 5.7°C below the ambient temperature, and an average cooling power of 62.7W / m 2 , indicating that the film has good radiative cooling capabilities. The film has a latent heat storage of 46.2 J / g. The error in the latent heat storage value of the film after 1000 temperature cycles is less than 10% compared to the film without temperature cycles, indicating that the film has good thermal reliability.
[0087] Figure 6 The actual image (a) and the microscopic morphology under a scanning electron microscope (b) of the electrospun film of Example 3 of the present invention are shown.
[0088] The fiber diameter of the electrospun film prepared in Example 2 of the present invention is 100 nm-3 μm, and the diameter of the microcapsule is 300 nm-10 μm.
[0089] Figure 7 FLIR image (a) and actual image (b) comparing the temperature difference effect of the electrospun film prepared in Example 3 of the present invention under direct sunlight.
[0090] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a polyvinyl alcohol composite silicon oxide microcapsule temperature control material, characterized in that: The following steps are involved: An emulsion of capric acid-stearic acid eutectic coated with nano-silicon oxide was prepared by Pickering emulsification method; mixing the emulsion with a polyvinyl alcohol solution to obtain an electrospinning solution; The electrostatic spinning solution is subjected to electrostatic spinning treatment to obtain a spinning membrane, which is the polyvinyl alcohol composite silicon oxide microcapsule temperature control material.
2. The preparation method according to claim 1, characterized in that: In the process of preparing the emulsion using the Pickering emulsification method, the mass ratio of water to capric acid-stearic acid eutectic is (50:50)-(95:5), and the mass ratio of water to silicon oxide is (100:1)-(100:10).
3. The preparation method according to claim 1, characterized in that: The concentration of polyvinyl alcohol in the electrostatic spinning solution is 4%-12%.
4. The preparation method according to claim 1, characterized in that: The concentration of the polyvinyl alcohol solution is 6%-15%.
5. The preparation method according to claim 1, characterized in that: The capric acid-stearic acid eutectic is a eutectic obtained by mixing n-decanoic acid and stearic acid at 80° C.-90° C.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the decanoic acid to the stearic acid is (4:6)-(9:1).
7. The preparation method according to claim 1, characterized in that: The voltage of the electrospinning process is 20 kV-50 kV.
8. The preparation method according to claim 1, characterized in that: The thickness of the polyvinyl alcohol composite silicon oxide microcapsule temperature control material is 300 μm-1000 μm.
9. The polyvinyl alcohol composite silicon oxide microcapsule temperature control material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method and application for fatty acid / polymer shaped phase-change superfine complex fiber
CN102605463A
Silicon dioxide / CA-LA-PA / PET composite phase-changing fibers and preparation method thereof
CN109111900A
Phase-change microcapsule based on inorganic shell layer and preparation method and application thereof
CN111621265A
Colorful radiation refrigeration flexible composite film and preparation method thereof
CN111996679A
Fabric and preparation method thereof
CN118109925A